Building social and emotional competencies in elementary teachers through movement and mindfulness: a case study from Pakistan - Khan, Ramsha Usman (My University, 2025)
Teacher well-being is foundational to effective teaching, yet it remains underemphasized in both policy and school reform efforts, particularly in the Global South. When teachers feel emotionally supported, regulated, and reflective, they cultivate classroom environments that promote student belonging, resilience, and academic engagement. Culturally adapted Social and Emotional Learning (SEL), mindfulness, and movement-based practices offer meaningful and contextually relevant pathways for strengthening teachers’ social and emotional competencies in ways that honor local values, languages, and lived realities. Grounded in the CASEL framework and principles of mindfulness and informed by Ecological Systems Theory and the Prosocial Classroom Model, this study examined how cultivating teacher well-being can influence personal growth, professional practice, and the broader educational ecosystem. This qualitative intervention case study, conducted over one academic year (September 2024–May 2025), involved eight elementary teachers at Chand Bagh Day School (CBDS) in Muridke, Pakistan. The research explored four questions: (1) How does SEL, mindfulness, and movement training impact teachers’ self-perception of well-being? (2) In what ways, if any, do teachers integrate these practices into personal life, and what challenges emerge if they do not? (3) In what ways, if any, do teachers integrate these practices into their classrooms, and what barriers hinder implementation? (4) What forms of support do teachers need to sustain SEL and mindfulness in the long term? Findings indicated meaningful personal and professional gains. Personally, teachers reported increased emotional literacy, greater self-awareness, improved emotional regulation, and stronger relationships with family and peers. Professionally, teachers described enhanced confidence, more positive classroom climates, improved classroom management, and closer student–teacher relationships. Despite these gains, challenges such as time constraints, limited conceptual understanding, and external disruptions, including school closures due to climate events or political instability, affected consistency. Teachers emphasized the need for ongoing coaching, subject-specific models, structured planning time, and school-wide adoption to sustain these practices. This study demonstrates the transformative potential of culturally adapted SEL, mindfulness, and movement-based interventions for promoting teacher well-being in non-Western contexts. It contributes to the growing discourse on contextualized SEL implementation and highlights the importance of supporting teachers as whole human beings in efforts to improve educational quality and equity.
Keywords: Social and emotional learning; Mindfulness; Elementary teachers; Case study; Educators; Pakistan